Reconstruction of Environmentally Conscious Mining Regulations in Indonesia: Perspectives from Islamic Legal Philosophy - Bayangsari Wedhatami; Ayup Suran Ningsih (NOVUM : JURNAL HUKUM, 2025)
Mining can be understood as the act of extracting non-renewable natural resources from within the earth. In Indonesia, mining is intended to achieve the greatest possible prosperity and well-being for the people. This research, focusing on the reconstruction of environmentally sound mining regulations in Indonesia from the perspective of Islamic legal philosophy, is a normative legal study based on doctrinal analysis with a philosophical approach as the primary method. The research findings emphasize that the urgency of environmentally sound mining regulations in Indonesia becomes highly significant when viewed from the perspective of Islamic legal philosophy, particularly the concept of hifdzul bi'ah within the maqashid syariah, which emphasizes human responsibility as a caliph to maintain ecological balance and protect the environment. Given the extractive nature of mining, which has a negative impact on ecosystems, strict regulations and comprehensive oversight are needed to ensure that mining practices do not conflict with Sharia principles regarding environmental preservation. Reconstruction of mining regulations based on the philosophy of hifdzul bi'ah (environmental protection), with a focusfocusing on explicitly integrating the principles of sustainability, social justice, and ecological responsibility into the regulations. The concrete strategies put forward include improving reclamation and post-mining regulations, implementing environmental impact assessments that incorporate Islamic values, enforcing fair and firm sanctions, and providing incentives for eco-friendly mining innovations.